AKTIVITAS ANTIMIKROBA BAKTERI ASAM LAKTAT YANG DIISOLASI DARI AIR SUSU IBU (ASI) TERHADAP BAKTERI PATOGEN Vibrio cholerae - Vinanta Agus Putra, Putu; Ekawati, I Gusti Ayu; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2015)
This study aims to determine the antimicrobial activity produced by lactic acid bacteria isolated from breast milk (ASI) against pathogenic bacteria Vibrio cholerae. The research design used in this study is the experimental method with 3 treatments, antimicrobial activity FCS (Free Cell Supernatant), FCSN (Free Cell Supernatant Neutral), and FCSHN (Free Cell Supernatants were Heated Neutral). The variables measured were the formation of inhibition zones produced by the presence of the antimicrobial activity of 9 isolates of LAB against pathogenic bacteria Vibrio cholerae . Data were presented in tables and figure and descriptive discussed. The results showed that the inhibitory activity against pathogenic bacteria Vibrio cholerae on FCS to isolate the A1, A3, A6, and B10b each produce inhibition diameter is 2.35 mm, 2.95 mm, 2.75 mm and 1.90 mm. the treatment FCSN inhibitory activity shown by A1 isolates diameter is 1.40 mm inhibition, and isolates A6 inhibition diameter is 1.00 mm. whereas the inhibitory activity on FCSHN treatment indicated by A1 isolates inhibition diameter is 0.40 mm.
Keywords: Lactic Acid Bacteria, Breast milk, Antimicrobial activity, Vibrio cholerae.